Interfacial charge and energy transfer in van der Waals heterojunctions. Issue 3 (18th January 2022) - Hu, Zehua; Liu, Xue; Hernández‐Martínez, Pedro Ludwig; Zhang, Shishu; Gu, Peng; Du, Wei; Xu, Weigao; Demir, Hilmi Volkan; Liu, Haiyun; Xiong, Qihua
Abstract: Van der Waals heterojunctions are fast‐emerging quantum structures fabricated by the controlled stacking of two‐dimensional (2D) materials. Owing to the atomically thin thickness, their carrier properties are not only determined by the host material itself, but also defined by the interlayer interactions, including dielectric environment, charge trapping centers, and stacking angles. The abundant constituents without the limitation of lattice constant matching enable fascinating electrical, optical, and magnetic properties in van der Waals heterojunctions toward next‐generation devices in photonics, optoelectronics, and information sciences. This review focuses on the charge and energy transfer processes and their dynamics in transition metal dichalcogenides (TMDCs), a family of quantum materials with strong excitonic effects and unique valley properties, and other related 2D materials such as graphene and hexagonal‐boron nitride. In the first part, we summarize the ultrafast charge transfer processes in van der Waals heterojunctions, including its experimental evidence and theoretical understanding, the interlayer excitons at the TMDC interfaces, and the hot carrier injection at the graphene/TMDCs interface. In the second part, the energy transfer, including both Förster and Dexter types, are reviewed from both experimental and theoretical perspectives. Finally, we highlight the typical charge and energy transfer applications in photodetectors and summarize the challenges and opportunities for future development in this field. Abstract : As a fast‐emerging platform, van der Waals heterojunctions have exhibited exotic carrier dynamics in the quantum limit, including charge and energy transfer. Based on the recent experimental and theoretical progress, this review summarizes the state‐of‐art understanding, followed by the representative applications in optoelectronic devices. We also summarize the remaining challenges and opportunities for future development in this field.